2010
DOI: 10.2165/11537960-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Drugs in Development for Influenza

Abstract: The emergence and global spread of the 2009 pandemic H1N1 influenza virus reminds us that we are limited in the strategies available to control influenza infection. Vaccines are the best option for the prophylaxis and control of a pandemic; however the lag time between virus identification and vaccine distribution exceeds six months and concerns of vaccine safety are a growing issue leading to vaccination refusal. In the short term, antiviral therapy is vital to control the spread of influenza; however, we are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
106
1
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 101 publications
0
106
1
9
Order By: Relevance
“…Significant effort is being devoted to developing new vaccine approaches to influenza (23,24), new inhibitors of viral targets (25), and novel strategies targeted at host factors (26,27). One host-targeted strategy is to suppress the availability of sialic acid receptors on the respiratory tract epithelium that are recognized by the influenza virus HA glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…Significant effort is being devoted to developing new vaccine approaches to influenza (23,24), new inhibitors of viral targets (25), and novel strategies targeted at host factors (26,27). One host-targeted strategy is to suppress the availability of sialic acid receptors on the respiratory tract epithelium that are recognized by the influenza virus HA glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…Progress in the development of influenza therapeutics accelerated after the emergence of highly pathogenic H5N1 influenza viruses in 1997 and the novel H1N1 pandemic influenza strain in 2009 (3,4). New strategies for the use of the currently licensed agents, including alternative forms of delivery and combination therapy with other drugs, are being explored (5). In addition, several novel antiviral compounds with different anti-influenza mechanisms are in various clinical phases of development.…”
mentioning
confidence: 99%
“…8) Though resistance to both antiviral classes has been increasingly documented globally, 9,10) some studies have indicated that amantadine-sensitive reassortant H1N1 virus became predominant in Japan during the 2007-2008 season. 11) Therefore, the M2 inhibitor appears to be potential in treating patients infected with these amantadine-sensitive viruses.…”
Section: )mentioning
confidence: 99%